2022
DOI: 10.3389/fimmu.2022.893929
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Oxidized Phospholipids in High-Density Lipoprotein During the Course of Sepsis and Their Prognostic Value

Abstract: PurposeTo examine the levels of 1-palmitoyl-2-(5-oxovaleroyl)-sn-glycero phosphatidylcholine (POVPC) and 1-palmitoyl-2-glutaroyl-sn-glycero-phosphatidylcholine (PGPC) (the oxidized phosphatidylcholines) in HDL during the course of sepsis and to evaluate their prognostic value.Materials and MethodsThis prospective cohort pilot study enrolled 25 septic patients and 10 healthy subjects from 2020 to 2021. The HDLs were extracted from patient plasmas at day 1, 3 and 7 after sepsis onset and from healthy plasmas (to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…There was an EPIC Norfolk study that proved levels of oxidized phospholipids in plasma are associated with an increased risk of coronary artery disease (CAD) ( 45 ). The studies showed that the total phospholipid level in the plasma of patients is higher than that in the plasma of healthy individuals ( 46 ). Previous studies have shown that PGPC concentrations in plasma from healthy controls range from 0.15 to 1 μM ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was an EPIC Norfolk study that proved levels of oxidized phospholipids in plasma are associated with an increased risk of coronary artery disease (CAD) ( 45 ). The studies showed that the total phospholipid level in the plasma of patients is higher than that in the plasma of healthy individuals ( 46 ). Previous studies have shown that PGPC concentrations in plasma from healthy controls range from 0.15 to 1 μM ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…No sample size limit was included due to limited literature. Biomarkers are presented in order of relative abundance in literature.bHDL level was measured as HDL associated cholesterol (HDL-C) in studies [93–96,98 ▪▪ ,101–103]. Other HDL quantification was assayed using various metabolomic methods.cLDL level was measured as LDL associated cholesterol (LDL-C) in studies [93,96,98 ▪▪ ,101].…”
Section: Lipid Biomarkersmentioning
confidence: 99%
“…HDL is involved in immune modulation through its binding and sequestration of bacterial lipopolysaccharide (LPS), reducing integrin activation on monocytes and neutrophils, and protecting the endothelium by modulating vascular tone [113 & ]. HDL can be quantified biochemically as HDL associated cholesterol (HDL-C) [93][94][95][96]98 && , [101][102][103] or by mass spectrometry [90,97]. HDL levels decline at the time of hospital admission in patients with sepsis [93][94][95][96][97][98][99] and are lower in critically ill patients with sepsis relative to those critically ill due to trauma [96] or critically ill due to a nonsepsis diagnosis [99].…”
Section: -9672mentioning
confidence: 99%
See 2 more Smart Citations